Two new species of lizards from the Liolaemus lineomaculatus section (Squamata: Iguania: Liolaemidae) from southern Patagonia - Breitman, Maria Florencia; Parra, Micaela; Pérez, Cristian Hernán Fulvio; Sites, Jr., Jack Walter (Zootaxa, 2011)
Two new species of the lineomaculatus clade of the Liolaemus lineomaculatus section are described from southern Patagonia in Argentina. Liolaemus morandae sp. nov. is found in S Chubut province and Liolaemus avilae sp. nov. inhabits NW Santa Cruz province. Several tests were performed to diagnose these new species as distinct lineages. Univariate analysis of variance (ANOVA), principal component analysis (PCA), discriminant function analysis (DFA), non-parametric multivariate analysis of variance (NPMANOVA), as well as a genetic characterization through molecular analysis of variance (AMOVA) were performed; genetic distances between described and these new species are reported. The new Liolaemus species differ from other members of the lineomaculatus group in morphometric, meristic, qualitative and genetic characters; moreover they inhabit different phytogeographical provinces and districts. With these descriptions, the number of species now recognized in the lineomaculatus section is twenty one (including one more description that is in press).